2022
DOI: 10.1007/s10460-021-10291-1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the pathways to women’s empowerment in Northern Ghana and the relationship with small-scale irrigation

Abstract: Women’s empowerment is often an important goal of development interventions. This paper explores local perceptions of empowerment in the Upper East Region of Ghana and the pathways through which small-scale irrigation intervention targeted to men and women farmers contributes to women’s empowerment. Using qualitative data collected with 144 farmers and traders through 28 individual interviews and 16 focus group discussions, this paper innovates a framework to integrate the linkages between small-scale irrigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 56 publications
0
4
0
1
Order By: Relevance
“…Kumar et al (2021) found that the participation of women in self-help groups increases empowerment, control over income and decision-making over credit. The participation of women in alternative livelihood activities improved their empowerment and decision-making abilities (Bryan and Garner, 2022;Lawson et al, 2020). Figure 5 shows that 56% of women who have control over the use of income are disempowered, 78.99% are disempowered in terms of access to productive resources as an index of empowerment; 60.2% of women in terms of access to credit are disempowered; 51.8% of women are empowered in terms of leadership roles and 53% of women are empowered with respect to decision making on their production activities.…”
Section: Resultsmentioning
confidence: 99%
“…Kumar et al (2021) found that the participation of women in self-help groups increases empowerment, control over income and decision-making over credit. The participation of women in alternative livelihood activities improved their empowerment and decision-making abilities (Bryan and Garner, 2022;Lawson et al, 2020). Figure 5 shows that 56% of women who have control over the use of income are disempowered, 78.99% are disempowered in terms of access to productive resources as an index of empowerment; 60.2% of women in terms of access to credit are disempowered; 51.8% of women are empowered in terms of leadership roles and 53% of women are empowered with respect to decision making on their production activities.…”
Section: Resultsmentioning
confidence: 99%
“…Padahal, keterlibatan istri petani dalam kegiatan pertanian sangat penting dalam mengurangi biaya produksi karena istri petani adalah salah satu sumber daya yang menyediakan tenaga kerja (Mulyana et al, 2021). Meskipun telah dilakukan banyak penelitian tentang peran wanita dalam pertanian, tantangan gender dan ketimpangan sumber daya masih menjadi permasalahan yang dihadapi di banyak negara (Bryan & Garner, 2022) (Ali et al, 2016), termasuk di Indonesia, dimana dalam aktivitas pertanian oleh perempuan dalam hal akses dan kontrol terhadap sumber daya pertanian, masih sangat didominasi oleh laki-laki (Puspitawati et al, 2019). Wanita juga dianggap kurang diuntungkan dibandingkan dengan laki-laki dalam hal beban kerja, waktu kerja, upah, manfaat teknologi, pengambilan keputusan, dan yang paling penting, hak atas properti dan tanah (Pattnaik & Lahiri-Dutt, 2020).…”
Section: Pendahuluanunclassified
“…Previous systematic reviews (see e.g., Nandi, 2021), in addition to impact evaluations (see e.g., Kihiu, 2021), have analyzed the effect of specific infrastructure on the outcome variables of interest (see also Bryan, 2022;Dinkelman, 2011;Mahmud, 2018;Passarelli, 2018;Stifel, 2017). This study is the first to provide comprehensive evidence and gap on the impact of a wider typology of infrastructure on nutrition, women empowerment, and gender equality in LMICs to inform research and evidence on the impact of infrastructure on nutritious diet, WEE, and gender equality.…”
Section: Why It Is Important To Develop the Egmmentioning
confidence: 99%